A corrected cake resistance expression by considering the deposition property of different feed suspensions/solutions. Issue 1 (2nd January 2021) - Wang, Zhan; Wang, Zhou; Hou, Lei; Ma, Yu; Wang, Xu; Yao, Wei
ABSTRACT: The influence of deposition property to the cake filtration process was considered and the deposition factor was introduced to correct cake resistance for dead-end mode at constant transmembrane pressure. The values of model parameters in the traditional and corrected cake resistance expressions were determined for activated sludge, yeast, kaolin suspensions, and humic acid solution, respectively. The higher adsorption and sedimentation ability will make the deposition factor bigger. In addition, the predictions of the corrected cake resistance expression are in good agreement with experimental data at different TMPs and concentrations. The applicability of the corrected cake resistance expression was also validated.